Band‐notched CPW‐FED UWB antenna using V‐shaped fractal elements. Issue 11 (November 2015) - Esmati, Zahra; Moosazadeh, Mahdi
ABSTRACT A simple procedure for designing a new fractal CPW‐fed monopole antenna with band‐notch function for ultrawideband applications has been proposed. The proposed antenna consists of V‐shaped patch with circular‐shaped elements and an elliptically‐shaped tapered ground plane. To create band‐notch function, V‐shaped structure is extruded on the patch from the throat of the feed. By cutting a pair of a quarter ellipse‐shaped slots in the ground plane, proper impedance matching is obtained; as a result much wider impedance bandwidth can be achieved, especially at the higher frequencies. The antenna is small in size (25 × 25 mm2) and has wide usable fractional bandwidth of more than 143% (3.15–19 GHz) defined by VSWR < 2, except at frequency band‐notched of 4.90–6.04 GHz. Moreover, Omnidirectional radiation pattern and acceptable antenna gain are obtained over the operating band. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2533–2536, 2015